Comparison of Lymphocyte Populations in Patients With Dobrava or Puumala orthohantavirus Infection - Resman Rus, Katarina; Kopitar, Andreja Nataša; Korva, Miša; Ihan, Alojz; Petrovec, Miroslav; Avšič-Županc, Tatjana (Frontiers in Cellular and Infection Microbiology, 2020)
Hemorrhagic fever with renal syndrome (HFRS), caused by Dobrava (DOBV) and Puumala (PUUV) orthohantaviruses, is an endemic disease in Slovenia. DOBV is mainly responsible for a more severe disease, whereas PUUV usually causes a milder form. Therefore, the aim of our study was to determine whether any differences in lymphocyte population in patients infected with these two viruses exist. Mononuclear cells from peripheral blood (PBMCs) were isolated from DOBV or PUUV infected patients and different lymphocyte subpopulations were analyzed with flow cytometry. Decreased concentrations of lymphocyte subpopulation were observed in DOBV and in PUUV infected patients compared with a healthy control, which was especially evident in DOBV infected patients. The lower values of T cells are likely due to the extravasation of the activated cells from the circulation to the infected tissue. Higher percentage of NK cells were detected in DOBV infected patients in comparison to PUUV infected patients, which could be associated with a more severe HFRS caused by DOBV. PUUV infected patients had a significantly higher concentration of activated T cell subsets, expressing markers CD25, CD69, and HLA-DR in comparison to DOBV infected patients. Higher activation of T cell subsets in PUUV infected patients could be a contributor to a milder HFRS. Further studies are necessary to elucidate the relation between the protective and the harmful role of activated lymphocytes subsets in HFRS pathogenesis.